1999
DOI: 10.1002/1529-0131(199908)42:8<1729::aid-anr23>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities of radiologic osteoarthritis in peripheral joints and of disc degeneration of the spine

Abstract: Objective. To estimate the genetic influence on the occurrence of radiologic osteoarthritis (ROA) in the knees, hips, and hands and disc degeneration of the spine in the general population. Methods. A random sample of 1,583 individuals was drawn to estimate the prevalence of ROA and disc degeneration in the general population. Of 118 pro-bands with multiple affected joint sites who were derived from this sample, we were able to recruit 257 siblings. The variance of ROA and disc degeneration within sibling pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 16 publications
3
77
0
5
Order By: Relevance
“…In a random sample of 809 unrelated subjects (the Rotterdam sample), ages 55 -65 years, radiographs were scored for the presence of ROA in two knees, two hips, 19 36 hand joints and three levels of the thoracocolumbar spine. 19,20 All radiographs were scored according to the Kellgren/Lawrence grading system (grades 0 -4) 17 by two independent readers, blinded to all other data of the participant. Definite ROA at a particular joint site was defined as a Kellgren/Lawrence score of two or more.…”
Section: The Rotterdam Samplementioning
confidence: 73%
“…In a random sample of 809 unrelated subjects (the Rotterdam sample), ages 55 -65 years, radiographs were scored for the presence of ROA in two knees, two hips, 19 36 hand joints and three levels of the thoracocolumbar spine. 19,20 All radiographs were scored according to the Kellgren/Lawrence grading system (grades 0 -4) 17 by two independent readers, blinded to all other data of the participant. Definite ROA at a particular joint site was defined as a Kellgren/Lawrence score of two or more.…”
Section: The Rotterdam Samplementioning
confidence: 73%
“…In epidemiological studies, the term is used to describe subjects with 2 -3 radiographically affected sites, which may occur relatively frequent at ages above 55 years when considering, for example, hand and spine. 2 In contrast, the diagnosis of FOA in our families reflect patients with early onset symptomatic polyarticular disease, affecting typical as well as atypical sites and occurs in an autosomal-dominant inheritance patterns. 13 Such a specific phenotype is rare, however, emerged after radiographic and physical examination as homogeneous among our family members.…”
Section: Discussionmentioning
confidence: 99%
“…In a random sample of 1369 unrelated subjects (the Rotterdam sample), aged 55 -70 years, radiographs were scored for the presence of ROA in two knees, two hips, 16 36 hand joints and three levels of the thoracocolumbar spine. 2 All radiographs were scored according to the Kellgren's criteria 14 by two independent readers, blinded to all other data of the participant. Definite ROA was defined as a Kellgren's score of Z2.…”
Section: The Rotterdam Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that both hand OA and hip OA are highly heritable (4-6), more so than knee OA (7). If genetic predisposition accounts for the low prevalence of hip OA in the Chinese, we might expect that the Chinese would also have a lower prevalence of hand OA than that among whites.…”
mentioning
confidence: 99%